1993
DOI: 10.1159/000118956
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid Personality Traits and Psychosomatic Background Factors in Depression: The Lundby Study 1957–1972

Abstract: The search for specific predepressive personality factors has a long tradition in psychiatry. Studies in which assessments were made prospectively, before the onset of a first-ever episode of the illness, are, however, rare. In the present report from the Lundby Study we have investigated premorbid, mainly personality-related background factors for first incidences of depressive disorder, diagnosed according to the Lundby criteria for ‘Depression proper’ and ‘Depression plus other psychiatric symptoms’. The it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…In the predictor study on male car owners from Gothenburg [1], subclinical psychasthenic traits played a predisposing role for anxiety states. In ret rospectively assessed anxious patients, anergia has been noted as a predisposing feature [9], However, several authors have found that asthenia is an unspecific trait pre disposing to mental illness in general [15,30] and espe cially to depression [1,29], 'Lability of the autonomic nervous system' was in the present study found to be associated with an increased female vulnerability for anxiety. This feature had a signif icant predictive influence on anxiety in the study on male military conscripts by Angst and Vollrath [2], Other stud ies by Rorsman et al [29], Angst and Clayton [31] and Clayton et al [32] show, however, that this is a predictive feature of depression as well.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In the predictor study on male car owners from Gothenburg [1], subclinical psychasthenic traits played a predisposing role for anxiety states. In ret rospectively assessed anxious patients, anergia has been noted as a predisposing feature [9], However, several authors have found that asthenia is an unspecific trait pre disposing to mental illness in general [15,30] and espe cially to depression [1,29], 'Lability of the autonomic nervous system' was in the present study found to be associated with an increased female vulnerability for anxiety. This feature had a signif icant predictive influence on anxiety in the study on male military conscripts by Angst and Vollrath [2], Other stud ies by Rorsman et al [29], Angst and Clayton [31] and Clayton et al [32] show, however, that this is a predictive feature of depression as well.…”
Section: Discussioncontrasting
confidence: 61%
“…As a consequence, investigators engaged in the Lundby Study have from the very beginning been just as interested in those apparently healthy in the population as in those apparently mentally ill. In earlier studies from Lundby we have analysed predisposing factors for mental illness in general, for alcoholism, for senile and vascular dementia and for depression [15,[21][22][23][24][25][26][27][28][29], The present investigation is the first Lundby substudy that deals specifically with background factors for anxiety disorder. Except for the variable 'age in 1947', the two sexes showed different types of predictive background factors, all of them representing various personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…This association between PE and depression has been replicated in both community and clinical adult samples (Brown, Chorpita, & Barlow 1998; Trull & Sher, 1994). Longitudinal studies also implicate low PE as a risk factor for onset of MDD later in life (Boyce et al, 1991; Clayton, Ernst, & Angst 1994 ; Rorsman, Grasbeck, Hagnell, Isberg, & Otterbeck 1993). …”
Section: Emotional Reactivity and Depressionmentioning
confidence: 99%
“…According to Angst and Clayton (1986) unipolar depressives scored high in aggression and autonomic lability. Elevated levels of autonomic lability or of neuroticism were also found by Maier et al (1992), Rorsman et al (1993), Kendler et al (1993), Clayton et al (1994), Lauer et al (1997), Surtees and Wainwright (1996), and Boyce et al (1991). In addition to this personality trait, Maier et al (1992) found elevated levels of rigidity and lowered levels of extraversion and frustration tolerance.…”
mentioning
confidence: 82%
“…Lauer et al (1997) confirmed the elevated scores on rigidity. Also reported were -besides rigidity -lack of confidence (Surtees and Wainwright, 1996), affective personality traits, asthenia, subjective asthenic symptoms, a tendency to be easily strained and to ruminate (Rorsman et al, 1993), high interpersonal sensitivity (Boyce et al, 1991), lower emotional strength, resiliency, interpersonal dependency and increased thoughtfulness.…”
mentioning
confidence: 99%